Assessment of adherence to dietary phosphate restrictions in the correction of hyperphosphatemia in dialysis patients - V. S. Sosnina; S. V. Malchikova (Лечащий Врач)
The adherence to a low-phosphate diet in the daily life of dialysis patients was evaluated. The study included 102 patients on renal replacement therapy with programmed hemodialysis. According to the survey, analysis of adherence to a low-phosphate diet by patients was performed. The main causes of non-compliance of patients with low phosphate diets were identified. It was revealed that patients on renal replacement therapy with programmed hemodialysis do not stick to the low-phosphate diet to full extent.